Laser-induced graphene on additive manufacturing parts - Chua, Zhong Yang (2019)
Additive manufacturing (AM) has become more prominent in leading industries. Recently, there have been intense efforts to achieve a fully functional 3D structural electronic device by integrating conductive structures into AM parts. Here, we introduce a simple approach to creating a conductive layer on a polymer AM part by CO2 laser processing. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Raman spectroscopy were employed to analyze laser-induced modifications in surface morphology and surface chemistry. The results suggest that conductive porous graphene was obtained from the AM-produced carbon precursor after the CO2 laser scanning. At a laser power of 4.5 W, the lowest sheet resistance of 15.9 Ω/sq was obtained, indicating the excellent electrical conductivity of the laser-induced graphene (LIG). The conductive graphene on the AM parts could serve as an electrical interconnection and shows a potential for the manufacturing of electronics components. An interdigital electrode capacitor was written on the AM parts to demonstrate the capability of LIG. Cyclic voltammetry, galvanostatic charge-discharge, and cyclability testing demonstrated good electrochemical performance of the LIG capacitor. These findings may create opportunities for the integration of laser direct writing electronic and additive manufacturing.